Carriage of Streptococcus pneumoniae, Haemophilus influenzae, Moraxella catarrhalis, and Staphylococcus aureus in Indonesian children: A cross-sectional study - Dunne, Eileen M.; Murad, Chrysanti; Sudigdoadi, Sunaryati; Fadlyana, Eddy; Tarigan, Rodman; Indriyani, Sang Ayu Kompiyang; Pell, Casey L.; Watts, Emma; Satzke, Catherine; Hinds, Jason; Dewi, Nurhandini Eka; Yani, Finny Fitry; et al. (PloS one, 2018)
Streptococcus pneumoniae is an important cause of infection and commonly colonizes the nasopharynx of young children, along with other potentially pathogenic bacteria. The objectives of this study were to estimate the carriage prevalence of S. pneumoniae, Haemophilus influenzae, Moraxella catarrhalis, and Staphylococcus aureus in young children in Indonesia, and to examine interactions between these bacterial species. 302 healthy children aged 12-24 months were enrolled in community health centers in the Bandung, Central Lombok, and Padang regions. Nasopharyngeal swabs were collected and stored according to World Health Organization recommendations, and bacterial species detected by qPCR. Pneumococcal serotyping was conducted by microarray and latex agglutination/Quellung. Overall carriage prevalence was 49.5% for S. pneumoniae, 27.5% for H. influenzae, 42.7% for M. catarrhalis, and 7.3% for S. aureus. Prevalence of M. catarrhalis and S. pneumoniae, as well as pneumococcal serotype distribution, varied by region. Positive associations were observed for S. pneumoniae and M. catarrhalis (OR 3.07 [95%CI 1.91-4.94]), and H. influenzae and M. catarrhalis (OR 2.34 [95%CI 1.40-3.91]), and a negative association was found between M. catarrhalis and S. aureus (OR 0.06 [95%CI 0.01-0.43]). Densities of S. pneumoniae, H. influenzae, and M. catarrhalis were positively correlated when two of these species were present. Prior to pneumococcal vaccine introduction, pneumococcal carriage prevalence and serotype distribution varies among children living in different regions of Indonesia. Positive associations in both carriage and density identified among S. pneumoniae, H. influenzae, and M. catarrhalis suggest a synergistic relationship among these species with potential clinical implications.